Examining household relocation pressures from rising transport and housing costs – An Australian case study. (July 2018) - Li, Tiebei; Dodson, Jago; Sipe, Neil
Abstract: Increasing global energy prices have created serious pressure on transport and energy in Australian cities. The rising cost of transport and energy, combined with the price of housing in metropolitan areas, has placed households under greater economic pressure. This paper investigates how increased household transport costs interact with housing costs in Brisbane, Australia. Drawing on data from journey to work and Australia's Green Vehicle Guide, we estimated household transport costs associated with private vehicle fuel use for work travel. By linking household transport costs with housing costs across urban areas we were able to explore: 1) the spatial relationship between household transport fuel costs and direct spending on housing; and 2) areas of households under the highest pressure from transport costs and housing costs. We then estimated how rising fuel prices in Brisbane were likely to affect household housing location. We consider the trends of transport and housing costs and how they might affect urban spatial structure in the future. Highlights: Location strongly affects households' expenditure on transport and housing. Higher transport costs in outer areas are cause high risks for low income households. Urban expansion may slow down due to fuel cost increases.